A concise review of bioanalytical methods of small molecule immuno‐oncology drugs in cancer therapy. (24th November 2020) - Sulochana, Suresh P.; Trivedi, Ravi Kumar; Srinivas, Nuggehally R.; Mullangi, Ramesh
Abstract: Immuno‐oncology (IO) is an emerging option to treat cancer malignancies. In the last two years, IO has accounted for more than 90% of the new active drugs in various therapeutic indications of oncology drug development. Bioanalytical methods used for the quantitation of various IO small molecule drugs have been summarized in this review. The most commonly used are HPLC and LC–MS/MS methods. Determination of IO drugs from biological matrices involves drug extraction from the biological matrix, which is mostly achieved by simple protein precipitation, liquid–liquid extraction and solid‐phase extraction. Subsequently, quantitation is usually achieved by LC–MS/MS, but HPLC–UV has also been employed. The bioanalytical methods reported for each drug are briefly discussed and tabulated for easy access. Our review indicates that LC–MS/MS is a versatile and reliable tool for the sensitive, rapid and robust quantitation of IO drugs.